Impact of aging population on labour market in Turkey - Fırıncıoğulları, Şahsenem (2025)
This thesis examines the impact of demographic aging on the labor market in Türkiye, with comparative insights drawn from Sweden, Spain, and Romania. As Türkiye experiences a demographic transition marked by declining fertility rates and rising life expectancy, the country faces an inevitable shift in its labor force composition and pension sustainability. The study investigates key indicators such as the old-age dependency ratio, labor force participation, unemployment rates, and pension system dynamics. Through historical analysis and future projections, the research highlights how Türkiye, while currently younger than many European counterparts, is on a path toward similar demographic challenges. Using time lag analysis, the study quantifies the delay in Türkiye’s aging trajectory relative to benchmark countries and evaluates labor market resilience. The findings suggest that unless proactive policies are implemented, Türkiye may encounter increasing pressure on its labor supply and pension systems in the future. The thesis proposes policy recommendations inspired by European practices, aiming to improve participation rates, reform pension models, and manage migration effectively. By offering a comparative and forward-looking approach, this study contributes to understanding how Türkiye can better prepare for the socioeconomic consequences of an aging population.